Quranic verse finder: a tool for speech preparation using quranic verses - Maslina Abdul Aziz; Irfan Fikri Azni; Wan Faezah Abbas; Mohd Izuan Hafez; Nur Nafhatun Md Shariff (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper presents a mobile application called the Quranic Verse Finder. The main idea of this study is to develop a mobile application to help preachers in preparing their speech text. Based on preliminary investigation, the minimum time for a preacher to prepare a speech for a given topic is 3 hours. This process is very time consuming since the speech needs to refer to different source of reference such as the Quran and Hadith. The existing Quran search on the website or mobile application are from unknown source of reference. Therefore, to solve the problems mentioned above, this application offers an efficient method to search and identify any Quran verses for reference. With this application, the user can identify the juz number, the name of the Surah, which number of verses in the Surah and the meaning of the verses of a specific verse. The Quranic Verse Finder is different from other existing Quran Search applications due to its bilanguage feature. This application provides Malay and English translation. It also has other special features such as Bookmark that allows specific Quran verse to be saved for later reference. Moreover, due to the current trends, the Quranic Verse Finder allows user to share it using popular social media sites such as Facebook and Twitter.